Puzzle Media on Student Learning Outcomes in Science Learning in Class V of State Primary School 125138 Pematang Siantar - Winalda Sinurat; Yanti Arasi Sidabutar; Hetdy Sitio (MultiTech Publisher, 2023)
Study This examine The Influence of Puzzle Media to Results Study Student on social studies learning in Class V of SD Negeri 125838 Pematang Siantar . Problem in study This are : Students appear less active during the learning process , Teachers have not used learning media optimally so learning is less interesting or less effective , Teachers do not involve students in the learning process so learning is teacher-centred , Low learning outcomes for class V students at SD Negeri 125138 Pematang Siantar . Type research carried out is experiment with approach quantitative , with method Pre-Experiment designs . Population in study This is whole student class v elementary school at 125138 Pematang Siantar . As for who became sample is student class v 125138. Engineering deep data collection study This observation , test results Study And documentation . Technique data analysis consists from Test Normality , Test Hypothesis . Results study show that : the use of puzzle media in social studies learning in class v SD Negeri 125138 Pematang Siantar give influence positive to enhancement results Study increasing students _ so that give significant influence.